Expert System for Diagnosing Lovebird Bird Disease - R. Mohamed, Rajina; A. Mohamed, Mohamad; Cahyo Nugroho, Yuli; Hashim, Wahidah; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2019)
Lovebird is one of the chirping birds that is popular in the community now, besides its melodious voice and beautiful color. Not a few farmers who want to try cultivating this type of birds, but some of the farmers who just started are less likely to understand what kind of disease can attack Lovebird. Farmers can even have lose about this. Therefore, the expert system to diagnosis Lovebird disease is made. The expert system to diagnosis Lovebird disease is a web-based application, while in its design using SDLC/WATERFALL, taking one of the samples of the disease is worm disease. With the expert system in diagnosing the disease, it is expected to help the farmers to know and handle the affected Lovebird and also the results of the possible percentage will be displayed also in this expert system.